<span>18z-7(-3+2z)
= 18z + 21 - 14z
= 4z + 21
answer is False
</span><span>coefficient of z is 4, not 13</span>
Answer:
82
Step-by-step explanation:
hope this helps you man
For this case we have a function of the form:
![y = A * (b) ^ x ](https://tex.z-dn.net/?f=y%20%3D%20A%20%2A%20%28b%29%20%5E%20x%0A)
Where,
A: initial amount
b: decrease rate
x: time in days
Substituting values we have:
![y = 40 * (0.85) ^ x ](https://tex.z-dn.net/?f=y%20%3D%2040%20%2A%20%280.85%29%20%5E%20x%0A)
Therefore, the graph of the function is a decreasing exponential function in the first quadrant and that has an initial value of 40.
Answer:
graph of exponential function going from left to right in quadrant 1 through the point 0, 40 and approaching the x axis
32 = 8 x 4 I think that is the answer